Phagocytosis and Inflammation: Exploring the effects of the components of E‐cigarette vapor on macrophages. Issue 16 (4th September 2017) - Ween, Miranda P.; Whittall, Jonathan J.; Hamon, Rhys; Reynolds, Paul N.; Hodge, Sandra J.
Abstract: E‐cigarettes are perceived as harmless; however, evidence of their safety is lacking. New data suggests E‐cigarettes discharge a range of compounds capable of physiological damage to users. We previously established that cigarette smoke caused defective alveolar macrophage phagocytosis. The present study compared the effect E‐cigarette of components; E‐liquid flavors, nicotine, vegetable glycerine, and propylene glycol on phagocytosis, proinflammatory cytokine secretion, and phagocytic recognition molecule expression using differentiated THP‐1 macrophages. Similar to CSE, phagocytosis of NTHi bacteria was significantly decreased by E‐liquid flavoring (11.65–15.75%) versus control (27.01%). Nicotine also decreased phagocytosis (15.26%). E‐liquid, nicotine, and E‐liquid+ nicotine reduced phagocytic recognition molecules; SR‐A1 and TLR‐2. IL‐8 secretion increased with flavor and nicotine, while TNF α, IL‐1 β, IL‐6, MIP‐1 α, MIP‐1 β, and MCP‐1 decreased after exposure to most flavors and nicotine. PG, VG, or PG:VG mix also induced a decrease in MIP‐1 α and MIP‐1 β . We conclude that E‐cigarettes can cause macrophage phagocytic dysfunction, expression of phagocytic recognition receptors and cytokine secretion pathways. As such, E‐cigarettes should be treated with caution by users, especially those who are nonsmokers. Abstract : E‐cigarettes are marketed as a safer alternative to tobacco cigarettes, however the number of nonsmokers using E‐cigarettes is steadily rising, especially amongst youth. We investigated the effect of E‐cigarettes on healthy cells. We discovered that E‐cigarettes altered the phagocyotsis of pathogenic bacteria by macrophages via reduced expression of surface recognition receptors.